The Relationship of Family Support with the Quality of Life of The Elderly WHO Have Hypertension - Sumiyati; Ariani; M.Syikir; Suherman (Jurnal Life Birth, 2022)
Hypertension is a disorder of the circulatory system that often occurs in the elderly, with an increase in systolic blood pressure of more than 150 mmHg and diastolic blood pressure of more than 90 mmHg. The elderly who experience hypertension continuously and do not get treatment and proper control will cause the heart to work hard which then results in damage to the blood vessels of the heart, brain and eyes. The purpose of this study was to determine the relationship between family support and quality of life with hypertension. This research was conducted in Parondobulawan Village, Mamasa Regency, West Sulawesi. This study used a cross sectional research design. The independent variable in this study was the elderly or the elderly, while the independent variable was the quality of life of the elderly by measuring 4 dimensions of family support. The total population in this study was 165 people. Univariate analysis is used to see the characteristics of each respondent. Bivariate analysis using Chi-Square test. The results of this study are that there is a relationship between family support and the quality of life of the elderly with hypertension. The results are emotional support p-value 0.008, informational support p-value 0.005, instrumental support p-value 0.008 and reward support p-value 0.004 which means it is smaller. of (0.05). Thus it can be concluded that there is a significant relationship between the quality of life of the elderly who suffer from hypertension.